Le médecin généraliste face au certificat médical de non contre-indication à la pratique sportive: à propos d`une enquête de pratique - Redon, C.; Coudreuse, J.-M.; Pruvost, J.; Viton, J.-M.; Delarque, A.; Gentile, G. (Science & Sports, 2013)
Aims: In France, there are currently more that 15 million members of sports clubs or associations who require a medical certificate confirming that they have no medical conditions that would prevent them from practicing their chosen sport. This creates a large amount of work for the general practitioners in France who are required to carry out the examinations and issue these certificates. From literature searches, it is evident that there is no real consensus on how the examination should be carried out except in the case of professional or high-level sports players. It is therefore up to each individual doctor to decide how to proceed. Methods: In order to gain further insight into this question, a questionnaire was sent to general practitioners. The intention was to know the practice of general practitioners and find solutions to make this examination easier. Results: The results of this survey show that during the examination, general practitioners ask the patient a number of routine questions regarding their general state of health and carry out a complete clinical examination. However, there are evidently some discrepancies in the search of the past history, in how the legislation is followed and which additional examinations are performed. The survey also revealed that most general practitioners think that it would be helpful if there were a well-defined protocol for this examination and that this would also result in a reduction in expenditure. The development of standardized procedures for data collection (SFMES form, patient's questionnaire) and a well-defined protocol for the examination, approved by the Ministry of Sport, would be a considerable help in facilitating the work of general practitioners.